2019
DOI: 10.1186/s13722-018-0129-x
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of pharmacotherapy for alcohol use disorder by justice-involved women in the Veterans Health Administration

Abstract: BackgroundAlcohol use disorder (AUD) and unhealthy drinking are prevalent among women involved in the criminal justice system and women military veterans. Pharmacotherapy—including naltrexone, topiramate, acamprosate, and disulfiram—for AUD is one form of effective treatment that is associated with better health and criminal justice outcomes. The current study examined the association of justice involvement with receipt of pharmacotherapy for AUD, as well as other patient factors that may explain variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Implementation efforts to improve uptake of evidencebased substance use disorder treatment will need to tackle these barriers to ensure criminal justice involved [17] demonstrated that people with both a substance use disorder and an incarceration history had higher odds of utilizing substance use disorder treatment compared to people who had a substance use disorder without a history of incarceration. Consistent with Tsai and Gu's results are the findings of Taylor et al 's [18] national study of women with alcohol use disorder who used the Veterans Health Administration for care. Receipt of pharmacotherapy for alcohol use disorder was more frequent among women veterans with recent criminal justice involvement compared to women veterans with no known justice involvement.…”
Section: Open Accesssupporting
confidence: 78%
See 1 more Smart Citation
“…Implementation efforts to improve uptake of evidencebased substance use disorder treatment will need to tackle these barriers to ensure criminal justice involved [17] demonstrated that people with both a substance use disorder and an incarceration history had higher odds of utilizing substance use disorder treatment compared to people who had a substance use disorder without a history of incarceration. Consistent with Tsai and Gu's results are the findings of Taylor et al 's [18] national study of women with alcohol use disorder who used the Veterans Health Administration for care. Receipt of pharmacotherapy for alcohol use disorder was more frequent among women veterans with recent criminal justice involvement compared to women veterans with no known justice involvement.…”
Section: Open Accesssupporting
confidence: 78%
“…Relationships between criminal justice and community agencies should be strengthened to ensure substance use disorder treatment is available immediately following exit from incarceration and responsive to individuals' lived experience. Finally, although patients with a criminal justice history engaged in more substance use disorder treatment than their non-involved counterparts [17,18], the high prevalence of substance use disorders suggests that…”
Section: Discussionmentioning
confidence: 99%
“…The first cluster represents a school of thought named Community, which focused on research topics related to the mental/behavioral issues of international students within their community. Researchers in this field often examined a certain group of international students, such as Asian students in Japan [ 35 ], Italian students [ 36 ], and American students [ 37 , 38 ]. Furthermore, within this school of thought, risky behaviors (e.g., alcoholic problems) as well as helpful behaviors creativity in Ballentine [ 39 ], that happened within the international students’ community were also being investigated.…”
Section: Resultsmentioning
confidence: 99%
“…As international students’ mental health is influenced by the interaction between the students’ mindset and the surrounding environment, this science mapping showed that recent research is focusing more on investigating these specific interactions, that have not been explored before. Secondly, the newer keywords on the science mapping also showed a stronger emphasis on modern issues that students are facing during their study: the focus on changes in the environment and behavioral problems such as problematic social media use [ 2 , 92 , 93 ], social drinking and gambling [ 38 ], [ 90 , 94 ] has increased in recent years. Environmental changes and adaptation problems such as COVID-19 [ 9 , 91 , 95 ], coping strategies [ 96 , 97 , 98 ], and homesickness [ 68 , 99 ] are also being emphasized.…”
Section: Resultsmentioning
confidence: 99%
“…The need to maintain program sustainability prompted vendors serving patients in rural areas to make interinstitutional connections with criminal justice agencies, while an urban vendor engaged with law enforcement officers to bring opioid offenders to ED for PRC contact and treatment rather than arresting and jailing them and to develop continued MOUD delivery through billing. Importantly, such connections may be preventive of opioid overdose and fatalities, given high rates of these among newly released inmates [ 27 ]. Having PRCs work with jail inmates with OUD also fits philosophically with PRC work with ED overdose patients in that jail inmates, like overdose patients, have experienced a dramatic negative event (being jailed) and may be particularly receptive to MOUD and other treatment services.…”
Section: Discussionmentioning
confidence: 99%